A carbon material composite and its preparation method and application

By copolymerizing the carbon material with the modified liquid coated with polymer, the carbon material composite is formed, which solves the problem of poor dispersion of carbon nanotubes in various systems, and realizes an efficient and low-cost preparation process, which improves dispersion and conductivity.

CN119752235APending Publication Date: 2025-04-04DONGGUAN RUITAI NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411898395.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Carbon nanotubes have poor dispersion in battery paste, coatings, plastics and various systems, resulting in limited performance. In the prior art, the carbon nanotube powder predispersion has high preparation cost, high energy consumption, low production capacity, and a low proportion of active ingredient content.

Method used

The carbon material composite is formed by mixing the carbon material with a modified liquid coated with a polymer for copolymerization. The composite includes a carbon material and a polymer coated on the surface of the carbon material. The polymer includes polyalkenyl toluene, polyalkyl methacrylate, etc., and surfactants such as cellulose derivatives, sodium oleate, etc. can also be added to improve dispersion.

Benefits of technology

This method effectively blocks the reaggregation phenomenon caused by van der Waals force during the transport process, improves the dispersion of the carbon material composite, reduces the preparation cost, simplifies the process flow, and maintains the conductive properties of the carbon nanotubes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752235A_ABST
    Figure CN119752235A_ABST
Patent Text Reader

Abstract

The present invention provides a carbon material composite and a preparation method and application thereof, belonging to the field of carbon materials. The present invention provides a carbon material composite, comprising a carbon material and a polymer coated on the surface of the carbon material; the polymer comprises one or more of polyalkenyltoluene, polyalkyl methacrylate, polyhydroxyalkyl methacrylate and polystyrene sulfonic acid. Coating the polymer on the surface of the carbon material powder effectively blocks the re-agglomeration phenomenon of the carbon material formed under the traction of the van der Waals force during transportation. Compared with conventional carbon nanotube powders, the carbon material composite provided by the present invention is easy to disperse and can be evenly distributed in the customer's product system without strong dispersion conditions, giving full play to the performance advantages of the carbon material composite; compared with commercially available carbon nanotube slurry, the carbon material composite provided by the present invention is solvent-free, easy to transport, low in cost, and widely applicable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of carbon materials, and in particular to a carbon material composite and a preparation method and application thereof. Background Art

[0002] Carbon nanotubes are a one-dimensional carbon material with sp 2 The hybridization forms a hexagonal lattice, and the carbon atoms are arranged regularly along the radial direction. Carbon nanotubes have shown great application potential in civilian products and military fields due to their unique electrical, thermal, chemical and mechanical properties.

[0003] The bond energy of carbon-carbon bonds in carbon nanotubes is relatively high, which gives carbon nanotubes ideal Young's modulus, hardness and toughness. When carbon nanotubes are bent by external forces, the bent parts become flat, but they do not break. Adding them to coatings can significantly improve the strength and toughness of the coating and prevent high-temperature cracking. The electron cloud on the hexagonal lattice in carbon nanotubes can form a delocalized large π bond, allowing electrons to be transmitted at ultra-fast speeds, allowing the static charge they carry to be quickly released. Therefore, adding carbon nanotubes to battery materials or polymer resins can form a continuous conductive network, in which carriers are transmitted, which can significantly improve the conductive properties of the battery or coating;

[0004] In summary, carbon nanotubes, as a new functional material, have a wide range of applications due to their unique structure and excellent performance. They have great potential for application in a variety of products or materials such as lithium battery conductive agents, conductive plastics, transparent conductive films, supercapacitors, conductive inks, antistatic coatings, and high-strength "super fibers".

[0005] However, carbon nanotubes have a huge aspect ratio and almost no functional groups on their surface, making them easily aggregated under the action of van der Waals forces. This results in poor dispersion in battery slurries, coatings, plastics and various systems, severely limiting the performance of carbon nanotubes and their application scenarios.

[0006] In the prior art, carbon nanotube powder is currently mainly pre-dispersed by grinding equipment. The carbon nanotube powder is pre-dispersed in a solvent to prepare a carbon nanotube pre-dispersion liquid, which is then dispersed and put into the battery assembly and coating industries. The preparation production line has a large investment cost, a long preparation time for the pre-dispersion liquid, high energy consumption, low production capacity, and high preparation cost. Moreover, 90% or more of the ingredients are N-methylpyrrolidone (NMP) or water, the content of effective ingredients is low, and the storage and transportation costs are high. Summary of the invention

[0007] The invention provides a carbon material composite and a preparation method and application thereof. The carbon material composite has good dispersibility.

[0008] The present invention provides a carbon material composite, comprising a carbon material and a polymer coated on the surface of the carbon material;

[0009] The polymer includes one or more of polyalkenyltoluene, polyalkyl methacrylate, polyhydroxyalkyl methacrylate and polystyrene sulfonic acid.

[0010] Preferably, the carbon material composite further comprises a surfactant dispersed in the polymer and / or located on the surface of the polymer.

[0011] Preferably, the surfactant includes one or more of cellulose derivatives, sodium oleate, polyvinyl pyrrolidone, polyvinyl alcohol, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and cetyltrimethylammonium bromide.

[0012] Preferably, the carbon material includes one or more of array carbon nanotubes, entangled carbon nanotubes, single-walled carbon nanotubes, double-walled carbon nanotubes, multi-walled carbon nanotubes and carbon black.

[0013] Preferably, the mass content of the carbon material in the carbon material composite is 50-95%.

[0014] Preferably, the polyalkenyltoluene includes polyvinyltoluene; the polyalkyl methacrylate includes polymethyl methacrylate; and the polyhydroxyalkyl methacrylate includes polyhydroxyethyl methacrylate.

[0015] The present invention also provides a method for preparing the carbon material composite described in the above technical solution, comprising the following steps:

[0016] The coating modification liquid containing polymer monomers and free radical initiators is mixed with the carbon material for copolymerization reaction to obtain the carbon material composite.

[0017] Preferably, before the mixing, the method further comprises: transporting the carbon material to a deagglomerator for dispersing and deagglomerating;

[0018] The dispersion line speed of the deagglomerator is 105-120 m / s, and the temperature of the deagglomeration is 115-130°C.

[0019] Preferably, the mixing comprises: atomizing the coating modification liquid and spraying it into a depolymerizer to mix with the dispersed and depolymerized carbon material.

[0020] The present invention also provides the use of the carbon material composite described in the above technical solution or the carbon material composite prepared by the preparation method described in the above technical solution in coatings, inks, conductive plastics or batteries.

[0021] In the present invention, coating the surface of the carbon material powder with a polymer can effectively prevent the reagglomeration of the carbon material formed under the traction of the van der Waals force during the transportation process.

[0022] Compared with conventional carbon nanotube powders, the carbon material composite provided by the present invention is easy to disperse and can be evenly distributed in the product system without strong dispersion conditions, thereby exerting the performance advantages of the carbon material composite; compared with commercially available carbon nanotube slurry, the carbon material composite provided by the present invention is solvent-free, easy to transport, low in cost, and has wide applicability.

[0023] Compared with the conventional carbon nanotube powder surface functional group grafting chemical modification method, the carbon material composite provided by the present invention will not reduce the conductivity of the powder itself, and can give full play to the performance advantages of carbon nanotubes.

[0024] The principle of preparing the carbon material composite in the depolymerizer of the present invention is as follows: the carbon material is broken up and depolymerized, and the atomized coating modification liquid gas is fully coated and fused with the depolymerized carbon material powder in the depolymerizer cavity, and the atomized monomer in the cavity is instantly in contact with and wetted with the depolymerized carbon material powder, and the active groups in the coating modification liquid undergo copolymerization reaction at high temperature to form a high molecular polymer, and a uniform coating layer is formed on the surface of the depolymerized carbon material powder, which blocks the re-agglomeration phenomenon of the carbon material powder formed under the traction of the van der Waals force due to the disappearance of shear force during the transportation process, thereby keeping the carbon material powder in a good and easy-to-disperse state, and the surfactant can physically isolate the carbon material composites to prevent the re-agglomeration of the powder after the shear force disappears, and the water vapor or solvent gas in the coating modification liquid is evaporated at high temperature by a heating system, and smoke separation is carried out in a bag filter box, and the gas is discharged through a fan, thereby keeping the effective component content of the powder in compliance with the standard requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a process flow chart for preparing a carbon material composite according to an embodiment of the present invention. DETAILED DESCRIPTION

[0026] The present invention provides a carbon material composite, comprising a carbon material and a polymer coated on the surface of the carbon material;

[0027] The polymer includes one or more of polyalkenyltoluene, polyalkyl methacrylate, polyhydroxyalkyl methacrylate and polystyrene sulfonic acid.

[0028] In the present invention, the carbon material composite also includes a surfactant dispersed in the polymer and / or located on the surface of the polymer; the mass of the surfactant is preferably 5 to 70% of the mass of the carbon material. In a specific embodiment of the present invention, the mass of the surfactant can be 5%, 15%, 25%, 35%, 45%, 55%, 65%, or 70% of the mass of the carbon material; the surfactant preferably includes one or more of cellulose derivatives, sodium oleate, polyvinyl pyrrolidone, polyvinyl alcohol, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and cetyltrimethylammonium bromide.

[0029] In the present invention, the mass content of the carbon material in the carbon material composite is preferably 50-95%. In a specific embodiment of the present invention, the mass content of the carbon material in the carbon material composite can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% or 95%; the carbon material includes one or more of array carbon nanotubes, entangled carbon nanotubes, single-walled carbon nanotubes, double-walled carbon nanotubes, multi-walled carbon nanotubes and carbon black.

[0030] The present invention also provides a method for preparing the carbon material composite described in the above technical solution, comprising the following steps:

[0031] The coating modification liquid containing polymer monomers and free radical initiators is mixed with the carbon material for copolymerization reaction to obtain the carbon material polymer.

[0032] In the present invention, the coating modification liquid preferably further comprises a surfactant. When the coating modification liquid further comprises a surfactant, the preparation method of the coating modification liquid preferably comprises the following steps:

[0033] The surfactant, the polymer monomer and the solvent are first mixed to obtain a first mixture;

[0034] The first mixture is secondarily mixed with a free radical initiator.

[0035] In the present invention, the mass ratio of the polymer monomer to the solvent is preferably 1:1.5-3. In a specific embodiment of the present invention, the mass ratio of the polymer monomer to the solvent can be 1:1.5, 1:2, 1:2.5, 1:2.75 or 1:3; the monomer of the polystyrene sulfonic acid preferably includes sodium styrene sulfonate; the solvent preferably includes one or more of ethanol, n-propanol, isopropanol, acetone, N-methylpyrrolidone, butanol, butanediol, pentane, n-hexane, cyclohexane, trichloroethane, carbon tetrachloride, ethyl acetate, methyl ethyl ketone, dimethylformamide, dimethylacetamide, benzene, xylene and water.

[0036] In the present invention, the preferred temperature for the first mixing is 60-80° C., and the preferred time is 2-3 hours. The present invention has no particular limitation on the stirring speed of the first mixing, and the surfactant and the polymer monomer can be dissolved in the solvent.

[0037] In the present invention, the first mixture is preferably cooled to 30-50° C. before the second mixing.

[0038] In the present invention, the mass of the free radical initiator is preferably 0.1-0.8% of the mass of the first mixture. In a specific embodiment of the present invention, the mass of the free radical initiator can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7% or 0.8% of the mass of the first mixture; the free radical initiator preferably includes a peroxide initiator, and the peroxide initiator preferably includes one or more of diisopropylbenzene peroxide, tert-butyl trimethylcyclohexane peroxide and tert-butyl perbenzoate.

[0039] In the present invention, the second mixing is preferably performed under stirring conditions, and the second mixing time is preferably 1 to 2 hours.

[0040] After the second mixing, the obtained mixture is preferably cooled to room temperature to obtain the coating modification liquid.

[0041] In the present invention, before the mixing, the process preferably further comprises: conveying the carbon material to a deagglomerator for dispersing and deagglomerating.

[0042] In the present invention, the dispersion line speed of the deagglomerator is preferably 105-120 m / s. In a specific embodiment of the present invention, the dispersion line speed of the deagglomerator can be 105 m / s, 110 m / s, 115 m / s or 120 m / s.

[0043] In the present invention, the temperature for breaking up and depolymerizing is preferably 110-180°C. In a specific embodiment of the present invention, the temperature for breaking up and depolymerizing can be 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C or 180°C.

[0044] Under the action of the high shear dispersing rotor of the deagglomerator, the carbon material powder is broken up and deagglomerated.

[0045] In the present invention, the mixing preferably comprises: atomizing the coating modification liquid and spraying it into a depolymerizer to mix with the dispersed and depolymerized carbon material.

[0046] In the present invention, the mass ratio of the polymer monomer to the carbon material is preferably 0.03 to 0.3:1. In a specific embodiment of the present invention, the mass ratio of the polymer monomer to the carbon material can be 0.03:1, 0.05:1, 0.09:1, 0.12:1, 0.15:1, 0.18:1, 0.21:1, 0.24:1, 0.28:1 or 0.3:1.

[0047] In the present invention, the diameter of the nozzle used for atomization is preferably 0.5 to 1.0 mm, and the pressure of atomization is preferably 0.2 to 0.4 MPa.

[0048] In the present invention, the mixing temperature is preferably 110-180°C. In a specific embodiment of the present invention, the mixing temperature may be 110, 115, 120, 125, 130, 135, 140, 145, 150, 155, 160, 165, 170, 175 or 180°C. The dispersion line speed of the depolymerizer during the mixing is preferably 105-120 m / s. In a specific embodiment of the present invention, the dispersion line speed of the depolymerizer may be 105 m / s, 110 m / s, 115 m / s or 120 m / s.

[0049] A copolymerization reaction occurs during the mixing process and is completed within 3 to 5 seconds.

[0050] The coating modification liquid is dispersed by atomization and fully coated and fused with the depolymerized carbon material. The atomized coating modification liquid instantly contacts and wets the depolymerized carbon material powder. The monomers in the coating modification liquid undergo copolymerization reaction at high temperature to form a polymer, and a uniform coating layer is formed on the surface of the depolymerized carbon material powder, thereby preventing the reagglomeration of the carbon material due to the disappearance of shear force under the traction of van der Waals force during transportation, thereby keeping the carbon material composite powder in a good and easy-to-disperse state; and the solvent in the coating modification liquid evaporates at high temperature (110-180°C) and is discharged through a fan, thereby obtaining the carbon material composite powder.

[0051] The present invention also provides the use of the carbon material composite described in the above technical solution or the carbon material composite prepared by the preparation method described in the above technical solution in coatings, inks, conductive plastics or batteries.

[0052] The process flow chart of preparing the carbon material composite according to the embodiment of the present invention is as follows: Figure 1As shown: After obtaining raw materials of carbon material powder and coating modification liquid, the coating modification liquid is prepared. The carbon material powder is added into the dispersion chamber, and the carbon material powder is dispersed and depolymerized under the conditions of specified temperature and linear speed. The coating modification liquid is atomized and fully wetted with the depolymerized carbon material powder in the chamber to form a coating layer. Under the conditions of specified temperature, the coating layer modifier undergoes copolymerization reaction to form a stable and uniform carbon material powder coating film layer. The smoke is transported to the bag filter box by a high-pressure fan to collect the powder sample, thereby obtaining an easily dispersible carbon material composite powder.

[0053] The carbon material composite provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0054] Example 1

[0055] The preparation method of the easily dispersible carbon material composite powder is as follows:

[0056] Add 2000 g of polyvinyl pyrrolidone, 1000 g of methyl methacrylate and 2000 g of toluene into a reaction tank, heat to 75° C., stir at constant temperature for 2.5 h, cool to 40° C., add 20.0 g of diisopropylbenzene peroxide, stir at constant temperature for 1.5 h, and obtain a coating modification liquid.

[0057] The heating system and operation system of the depolymerization and dispersion chamber were turned on until the dispersion linear velocity was stabilized at 105 m / s and the temperature was stabilized at 130 °C. Carbon nanotubes (with a tube diameter of 20 nm and a specific surface area of ​​193 m 2 / g, density is 0.10~0.12g / cm 3 ) 3000g, stably sprayed into the deagglomeration and dispersion chamber, and the carbon nanotube powder was dispersed and deagglomerated under high shear conditions;

[0058] The coating modification liquid is atomized by a gas atomization device (the diameter of the nozzle used is 0.8 mm, and the atomization pressure is 0.3 MPa) and then sprayed into the dispersion cavity to fully wet the depolymerized carbon nanotube powder in the cavity to form a coating layer. At the same time, at 130° C., the methyl methacrylate monomer covered by the coating layer copolymerizes to form a high molecular polymer, which effectively blocks the carbon nanotube powder from reaggregating under the action of van der Waals force after smoke transmission;

[0059] The flue gas is conveyed to the bag filter box by a high-pressure fan to collect the powder sample, thereby obtaining an easily dispersible carbon material composite powder.

[0060] Example 2

[0061] The preparation method of the easily dispersible carbon material composite powder is as follows:

[0062] Add 1500g of polyvinyl pyrrolidone, 500g of sodium dodecyl sulfate, 800g of sodium styrene sulfonate and 2200g of toluene into a reaction tank, heat to 72°C, stir at constant temperature for 2.8h, cool to 38°C, add 24.0g of tert-butyl peroxide trimethylcyclohexane, stir at constant temperature for 1.2h to obtain a coating modification liquid.

[0063] The heating system and operation system of the depolymerization and dispersion chamber were turned on until the dispersion linear velocity was stabilized at 115 m / s and the temperature was stabilized at 115 °C. Carbon nanotubes (with a tube diameter of 20 nm and a specific surface area of ​​193 m 2 / g, density is 0.10~0.12g / cm 3 ) 8400g, stably sprayed into the deagglomeration and dispersion chamber, and the carbon nanotube powder was dispersed and deagglomerated under high shear conditions;

[0064] The coating modification liquid is atomized by a gas atomization device (the diameter of the nozzle used is 1.0 mm, and the atomization pressure is 0.4 MPa) and then sprayed into the dispersion cavity to fully wet the depolymerized carbon nanotube powder in the cavity to form a coating layer. At the same time, at 115° C., the alkoxystyrene-styrene sulfonic acid copolymer covered by the coating layer is copolymerized to form a high molecular polymer, which effectively blocks the carbon nanotube powder from reaggregating under the action of van der Waals force after smoke transmission;

[0065] The flue gas is conveyed to the bag filter box by a high-pressure fan to collect the powder sample, thereby obtaining an easily dispersible carbon material composite powder.

[0066] Example 3

[0067] The preparation method of the easily dispersible carbon material composite powder is as follows:

[0068] Add 1500g of polyvinyl pyrrolidone, 500g of sodium dodecyl sulfate, 400g of sodium styrene sulfonate, 400g of vinyl toluene and 2200g of toluene into a reaction tank, heat to 75°C, stir at constant temperature for 3.0h, cool to 40°C, add 40.0g of tert-butyl peroxide trimethylcyclohexane, stir at constant temperature for 1.5h to obtain a coated modified liquid.

[0069] The heating system and operation system of the depolymerization and dispersion chamber were turned on until the dispersion line speed was stabilized at 120 m / s and the temperature was stabilized at 115 °C. Carbon nanotubes (with a tube diameter of 20 nm and a specific surface area of ​​193 m 2 / g, density is 0.10~0.12g / cm 3 )25200g, stably sprayed into the deagglomeration and dispersion chamber, and the carbon nanotube powder was dispersed and deagglomerated under high shear conditions;

[0070] The coating modification liquid is atomized by a gas atomization device (the diameter of the nozzle used is 0.5 mm, and the atomization pressure is 0.2 MPa) and then sprayed into the dispersion cavity to fully wet the depolymerized carbon nanotube powder in the cavity to form a coating layer. At the same time, at 115°C, the methyl methacrylate monomer covered by the coating layer copolymerizes to form a high molecular polymer, which effectively blocks the carbon nanotube powder from reaggregating under the action of van der Waals force after smoke transmission;

[0071] The flue gas is conveyed to the bag filter box by a high-pressure fan to collect the powder sample, thereby obtaining an easily dispersible carbon material composite powder.

[0072] Example 4

[0073] The preparation method of the easily dispersible carbon material composite powder is as follows:

[0074] Add 1500g of carboxymethyl cellulose, 500g of sodium dodecyl sulfate, 400g of sodium styrene sulfonate, 400g of vinyl toluene and 2200g of toluene into a reaction tank, heat to 75°C, stir at constant temperature for 3.0h, cool to 40°C, add 40.0g of tert-butyl peroxide trimethylcyclohexane, stir at constant temperature for 1.5h to obtain a coated modified liquid.

[0075] The heating system and operation system of the depolymerization and dispersion chamber were turned on until the dispersion line speed was stabilized at 120 m / s and the temperature was stabilized at 115 °C. Carbon nanotubes (with a tube diameter of 20 nm and a specific surface area of ​​193 m 2 / g, density is 0.10~0.12g / cm 3 )25200g, stably sprayed into the deagglomeration and dispersion chamber, and the carbon nanotube powder was dispersed and deagglomerated under high shear conditions;

[0076] The coating modification liquid is atomized by a gas atomization device (the diameter of the nozzle used is 0.5 mm, and the atomization pressure is 0.2 MPa) and then sprayed into the dispersion cavity to fully wet the depolymerized carbon nanotube powder in the cavity to form a coating layer. At the same time, at 115°C, the methyl methacrylate monomer covered by the coating layer copolymerizes to form a high molecular polymer, which effectively blocks the carbon nanotube powder from reaggregating under the action of van der Waals force after smoke transmission;

[0077] The flue gas is conveyed to the bag filter box by a high-pressure fan to collect the powder sample, thereby obtaining an easily dispersible carbon material composite powder.

[0078] Comparative Example 1

[0079] is the carbon nanotube powder used in the examples.

[0080] Comparative Example 2

[0081] The difference from Example 1 is that the carbon nanotube powder is not added with the composite coating liquid, but is directly dispersed and then collected to obtain the powder.

[0082] Comparative Example 3

[0083] 5 parts of the carbon nanotube powder used in the example, 1 part of polyvinyl pyrrolidone and 94 parts of NMP were wet-grinded in a sand mill chamber (speed of 600 rpm, time of 5 h, main machine operating current of 60 A) to obtain a carbon nanotube powder pre-dispersion liquid;

[0084] The carbon nanotube powder pre-dispersion liquid is dried to obtain powder.

[0085] The test methods of Examples 1 to 4 and Comparative Examples 1 to 3 are as follows:

[0086] Electrode sheet resistivity:

[0087] Prepare positive electrode slurry: weigh each material in a beaker according to the ratio of conductive agent (the conductive agent is the composite powder of Examples 1 to 4 and the powder in Comparative Examples 1 to 3): PVDF (polyvinylidene fluoride): single crystal nickel cobalt manganese ternary material (NCM523) = 0.7:1.5:97.8, and add solvent N-methylpyrrolidone to make the total solid content 70%.

[0088] A mechanical stirrer was used to disperse the mixture at a linear speed of 8 m / s for 150 min to obtain a positive electrode slurry;

[0089] Coating: Coat the prepared positive electrode slurry on the insulating film with a 200μm scraper to obtain a wet electrode film;

[0090] Drying: Place the electrode wet film in a 120℃ forced air drying oven and bake for 15 minutes to obtain a dried electrode;

[0091] Cutting and testing: Cut the dried electrode into samples of fixed size and use a four-probe resistivity tester to test the resistivity of the samples.

[0092] [Note] The electrode resistivity can be used to evaluate the dispersion degree of carbon nanotubes. The better the dispersion, the more complete the conductive network and the lower the resistivity.

[0093] Particle size D50 / D90:

[0094] The sample was diluted with deionized water to a solid content of 0.1%;

[0095] Use a laser particle size analyzer to test the sample particle size distribution and read the D50 and D90 values;

[0096] Particle sizes D50 and D90 can characterize the particle size of the sample.

[0097] Special note: The above test method is only used as a reference characterization method to prove the effects and advantages of the invention, and does not impose any limitation on the solution provided by the invention.

[0098] The experimental results are shown in Table 1.

[0099] Table 1 Experimental results of Examples 1 to 3 and Comparative Examples 1 to 3

[0100] Particle size D50 / μm Particle size D90 / μm Electrode resistivity / Ω.cm Example 1 10.22 20.728 25.12 Example 2 9.726 20.869 24.6 Example 3 7.468 14.857 22.09 Example 4 6.792 12.261 20.153 Comparative Example 1 94.97 320.619 No current (cannot be measured) Comparative Example 2 35.988 65.952 4337 Comparative Example 3 0.166 0.872 28.08

[0101] From the data in Table 1, we can see that:

[0102] The easily dispersible carbon material composite powder (Examples 1 to 4) provided by the present invention is easier to disperse than conventional carbon nanotubes (Comparative Example 1). The carbon nanotube composite powder can be well dispersed under simple stirring conditions (mechanical stirring at a linear speed of <10 m / s) and has a small particle size. It can be used in the positive electrode of a lithium ion battery to significantly reduce the resistivity of the electrode sheet.

[0103] Compared with the carbon nanotube powder that is only dispersed and depolymerized without coating (Comparative Example 2), the carbon nanotube composite powder has obvious conductivity advantages, is easier to disperse, and has better conductivity;

[0104] Compared with the carbon nanotube pre-dispersion liquid obtained by the conventional wet sand milling pulping process (Comparative Example 3), the conductivity of the easily dispersible carbon nanotube composite powder is better than that of the pre-dispersion liquid (the easily dispersible powder preparation process can retain a longer CNTs powder tube length), and there is no significant difference in dispersibility in the battery system with the pre-dispersion liquid. At the same time, it is solvent-free, and transportation and storage are more convenient and quick;

[0105] The method for preparing the easily dispersible carbon material composite powder mentioned above, the easily dispersible carbon material composite powder prepared by the present invention, through the combination of different types of polymers and surfactants, the powder is easily dispersed, can be directly applied to coatings, inks, conductive plastics, batteries and other industries, and is not affected by the solvent system used by customers, and can be used for products with different solvent systems of customers. The preparation process is simplified, and the solvent is omitted during transportation, which greatly reduces the transportation cost.

[0106] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A carbon material composite, characterized in that: Comprising a carbon material and a polymer coated on the surface of the carbon material; The polymer includes one or more of polyalkenyltoluene, polyalkyl methacrylate, polyhydroxyalkyl methacrylate and polystyrene sulfonic acid.

2. The carbon material composite according to claim 1, characterized in that: The carbon material composite further includes a surfactant dispersed in the polymer and / or located on the surface of the polymer.

3. The carbon material composite according to claim 2, characterized in that: The surfactant includes one or more of cellulose derivatives, sodium oleate, polyvinyl pyrrolidone, polyvinyl alcohol, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and cetyltrimethylammonium bromide.

4. The carbon material composite according to claim 1, characterized in that: The carbon material includes one or more of array carbon nanotubes, entangled carbon nanotubes, single-walled carbon nanotubes, double-walled carbon nanotubes, multi-walled carbon nanotubes and carbon black.

5. The carbon material composite according to claim 1 or 4, characterized in that: The mass content of the carbon material in the carbon material composite is 50-95%.

6. The carbon material composite according to claim 1, characterized in that: The polyalkenyltoluene includes polyvinyltoluene; the polyalkyl methacrylate includes polymethyl methacrylate; and the polyhydroxyalkyl methacrylate includes polyhydroxyethyl methacrylate.

7. The method for preparing the carbon material composite according to any one of claims 1 to 6, characterized in that: The following steps are involved: The coating modification liquid containing polymer monomers and free radical initiators is mixed with the carbon material for copolymerization reaction to obtain the carbon material composite.

8. The preparation method according to claim 7, characterized in that: Before the mixing, the method further includes: transporting the carbon material to a depolymerizer for dispersing and depolymerizing; The dispersion line speed of the deagglomerator is 105-120 m / s, and the temperature of the deagglomeration is 115-130°C.

9. The preparation method according to claim 8, characterized in that: The mixing comprises: atomizing the coating modification liquid and spraying it into a depolymerizer to mix with the dispersed and depolymerized carbon material.

10. Use of the carbon material composite according to any one of claims 1 to 6 or the carbon material composite prepared by the preparation method according to any one of claims 7 to 9 in coatings, inks, conductive plastics or batteries.